Modified lipoprotein-derived lipid particles accumulate in human stenotic aortic valves. - Satu Lehti (Public Library of Science (PLoS), 2013)
In aortic stenosis plasma lipoprotein-derived lipids accumulate in aortic valves. Here, we first compared the lipid compositions of stenotic aortic valves and atherosclerotic plaque cores. Both pathological tissues were found to be enriched in cholesteryl linoleate, a marker of extracellularly accumulated lipoproteins. In addition, a large proportion of the phospholipids were found to contain arachidonic acid, the common precursor of a number of proinflammatory lipid mediators. Next, we isolated and characterized extracellular lipid particles from human stenotic and non-stenotic control valves, and compared them to plasma lipoproteins from the same subjects. The extracellular valvular lipid particles were isolated from 15 stenotic and 14 non-stenotic aortic valves. Significantly more apoB-100-containing lipid particles were found in the stenotic than in the non-stenotic valves. The majority of the lipid particles isolated from the non-stenotic valves had sizes (23±6.2 nm in diameter) similar to those of plasma low density lipoprotein (LDL) (22±1.5 nm), while the lipid particles from stenotic valves were not of uniform size, their sizes ranging from 18 to more than 500 nm. The lipid particles showed signs of oxidative modifications, and when compared to isolated plasma LDL particles, the lipid particles isolated from the stenotic valves had a higher sphingomyelin/phosphatidylcholine -ratio, and also higher contents of lysophosphatidylcholine and unesterified cholesterol. The findings of the present study reveal, for the first time, that in stenotic human aortic valves, infiltrated plasma lipoproteins have undergone oxidative and lipolytic modifications, and become fused and aggregated. The generated large lipid particles may contribute to the pathogenesis of human aortic stenosis.